Entrepreneurs` Cognitive and Decision Making Styles - Motvaseli, Mahmoud; Lotfizadeh, Fariba (ASEAN Marketing Journal, 2021)
The main purpose of this study is to explore the relation between decision-making styles which are measured by the General decision-making style (GDMS) test and information processing styles which are often termed cognitive styles and are, in this study, measured by Cognitive Style Inventory. The authors directed a survey research on 162 Iranian students. Structural equation modeling techniques were used to measure the impact of cognitive styles on decision-making styles. The authors found that cognitive styles have a positive impact on decision-making styles. In spite of the abundant research on factors that affect decision-making styles, few researches have tested the relationship between cognitive styles and decision-making styles. This study examines the impact of cognitive styles on decision-making styles in Iran. This study, like most research paper studies, cannot easily be generalized. Furthermore, the results of this study could be affected by economic conditions.